Airspace Object Detection Above the Guarded Area Using Segmentation Neural Network - Štursa, Dominik; Doležel, Petr; Merta, Jan (Springer Nature Switzerland AG, 2021)
With the increasing number of drones and unmanned aerial vehicles (UAVs), more emphasis is placed on guarding of the airspace around private and also public buildings. In this contribution authors are introducing a complex multi-step approach for aerial objects detection. Introduced process is composed of a few consecutive steps, where objects are cropped from original input with use of cropping pattern provided by task of image segmentation. These objects are then classified and evaluated as a threat or not. However, the emphasis here is placed on the segmentation part only. Neural network topology, adopted from U-Net architecture, was proposed. Case study was made and discussed in an effort to cover a large number of possible states. The results of a proposed convolutional neural network architecture were compared with the U-Net architecture. Applying of the convolutional neural network to the task of airspace object detection lead to sufficiently precise results, thanks to which it is possible to assume the possibility of its use in the proposed multi-step detection system in further work.
Detekce objektů ve vzdušném prostoru nad střeženým prostorem pomocí segmentační neuronové sítě
Keywords: airspace guarding; convolutional neural network; object detection; U-Net; střežení vzdušného prostoru; konvoluční neuronová síť; detekce objektů; U-Net